KOMUNIKASI TRASENDENTAL - Nurhikmah Nurhikmah (Fakultas Ushuluddin, Adab, dan Dakwah IAIN Parepare, 2017)
Human ability to communicate is not limited to fellow human beings, but rather, also communicates with a Essence deemed to be God, God, or objects believed to have magical powers. Realization of human beliefs manifests slavery to God worthy of adoration through trasendental communication. Trasendental communication in Islam can be done through various media known as rituals of worship, both mandatory worship and worship of sunnah. Continuing worship is done in every day among other prayers